PENGARUH CSR TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING (PERUSAHAAN ANEKA INDUSTRI SEKTOR TEKSTIL DAN GARMENT TERDAFTAR DI BEI 2016-2018) - Sinaga, Eka Mayastika (Universitas Labuhanbatu, 2021)
This study aims to determine how the influence of corporate social responsibility on firm value with profitability as a moderating variable (Case Study of Various Industries in the Textile and Garment Sector Companies Listed on the Indonesia Stock Exchange 2016-2018 Period). The population in the study were various textile and garment industry companies listed on the Indonesia Stock Exchange (BEI) in the 2016-2018 period. The sampling method used was the purposive sampling method with a sample of 15 companies during the observation period of 3 consecutive years so that the total sample was 45. The method of analysis of this study used multiple linear regression and moderating regression analysis. The results of this study indicate that CSR and profitability have a significant effect on firm value.